Filming the line of control : the Indo-Pak relationship through the cinematic lens - Bharat, Meenakshi; Nirmal Kumar (b)
Charts out the history of the relationship between India and Pakistan as represented in cinema, especially in light of the improved political atmosphere between the two countries.